Biocatalysis: Chemical Biosynthesis - Codina, Agatha Bastida (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book has been written with the purpose of providing a vision of a topic which is on the edge of biology and chemistry. As well, we want to provide an updated vision of the potentials and limitations of biocatalysis, especially with respect to applications in processes of organic synthesis, fine chemicals, and medicine. This book pretends to illustrate the potential of an excellent overview of recent progress on the assessment of granted patents as a useful tool in asymmetric synthesis. Some distinguished researchers have contributed to this endeavor with their knowledge, their commitment and their encouragement